Why Do International Students Avoid Communicating with Americans? - Wang, I-Ching; Ahn, Janet N.; Kim, Hyojin J.; Lin-Siegler, Xiaodong (Journal of International Students, 2018)
We explore how the communication concerns of non-native English speakers (NNS) and Americans relate to their perceptions of each other and decisions to interact. NNS identified their concerns in communicating with Americans, the perceived causes of their concerns, and the strategies they would employ to address these concerns. Americans noted their perceptions of NNS’ (heavy and mild) accents and identified factors that influence their perceptions of NNS and decisions to communicate with NNS. Results revealed that the more NNS attribute their communication concerns to Americans’ bias, the more likely they would avoid interacting with Americans. Results also suggested that Americans show a more favorable attitude toward mild accent NNS. We discuss the implications these findings have for international education and future research.